MICROSOFT WORD SKILLS TRAINING FOR STUDENTS OF ISLAMIC HIGH SCHOOL WERU LOR, WEST JAVA, INDONESIA - Ade Johar Maturidi; Lilis Suharti; Moh Setiawan; M. Taufik Irfan (Ann Publisher, 2026)
Introduction. In the digital age, proficiency in digital technology, especially Microsoft Word, is an important skill for students to improve their academic and professional competence. To meet this need, a Microsoft Word training programme was implemented at SMA Islamiyah Weru Lor. This study aims to evaluate the effectiveness of the training in improving students' skills in utilising Microsoft Word features, including mail merge. Method. The training was conducted through three main stages: preparation, implementation, and evaluation. During the preparation stage, training needs were identified, and relevant materials were developed. The implementation stage employed a blended learning approach, combining theoretical explanations with hands-on practice to ensure students could effectively apply their knowledge. The evaluation stage was conducted through a post-training questionnaire to measure skill improvement. Results and Discussion. The results showed a significant improvement in students' abilities, with an average score of 3.77 out of 5, categorised as ‘good. The discussion highlighted that practical training methods contributed to a deeper understanding and more effective application of Microsoft Word tools. Additionally, the mail merge feature, which was previously unfamiliar to most participants, was successfully mastered by the majority. Conclusion. In conclusion, this training effectively improved students' digital literacy in the use of Microsoft Word. Future programmes should include more advanced features and longer training sessions to achieve a higher level of competence. The success of this initiative highlights the importance of structured digital skills training in educational institutions.